Dampak Deforestasi terhadap Laju Erosi dan Sedimentasi di Wilayah Perbukitan Indonesia: Tinjauan Literatur - Parid Pakaya; Frandika K. Toiyo; Mawardi Heru Prasetyo; Rahmawati A. Damiti; Sudarmanto Hasan; Marini Susanti Hamidun; Iswan Dunggio (Lembaga Pengembangan Kinerja Dosen, 2025)
Deforestation in Indonesia's hilly regions has a significant impact on increasing the rate of erosion and sedimentation. This study aims to systematically examine the effects of deforestation on erosion and sedimentation processes and evaluate conservation approaches used to mitigate these impacts. The method employed is a literature review of various relevant national and international studies, focusing on tropical upland areas in Indonesia. The analysis reveals that the conversion of forests into agricultural land, plantations, and settlements results in the loss of vegetative cover, which plays a critical role in stabilizing soil particles and regulating surface runoff. The resulting impacts include increased erosion rates, soil structure degradation, and elevated sedimentation in water bodies, which deteriorate water quality, reduce reservoir capacity, and harm aquatic ecosystems such as coral reefs and mangrove forests. Effective conservation approaches include vegetative techniques such as reforestation and agroforestry, as well as mechanical techniques such as terracing and check dams. The main recommendation from this review is the need for integrated conservation policies, community participation, and the mapping of vulnerable areas to achieve sustainable and adaptive land management in Indonesia’s hilly regions.